Structure and function of the Haemophilus influenzae autotransporters - Spahich, Nicole A.; St. Geme, III, Joseph W. (Frontiers in Cellular and Infection Microbiology, 2011)
Autotransporters are a large class of proteins that are found in the outer membrane of gram-negative bacteria and are almost universally implicated in virulence. These proteins consist of a C-terminal β-domain that is embedded in the outer membrane and an N-terminal domain that is exposed on the bacterial surface and is endowed with effector function. In this article, we review and compare the structural and functional characteristics of the Haemophilus influenzae IgA1 protease and Hap monomeric autotransporters and the H. influenzae Hia and Hsf trimeric autotransporters. All of these proteins play a role in colonization of the upper respiratory tract and in the pathogenesis of H. influenzae disease.